Rivalry or friendship? The development of the relationship of the headquarters of the Workers’ Gymnastic Unions to other gymnastic organisations in the Czech Lands in the years 1897–1939 (Theatrum historiae, 2023)
The study deals with the attitude of the Workers’ Gymnastic Unions (WGUs) towards other gymnastic associations in the Czech lands. These include Sokol, Orel, the Workers’ Federation/Proletarian Physical Education Federation, and the German Arbeiter-Turn und Sportverband. The study seeks an answer to the question of whether the opinions of WGU representatives towards these associations developed on the basis of their own will or external circumstances. Political parties had an important influence on their mutual relations. Thanks to the ideological connection with the relevant gymnastic associations, we can examine whether any opinion was shaped by party ideology. We will also be interested in any change of opinion and the reason for it.
Keywords: Arbeiter-Turn und Sportverband; Czech Lands; Czechoslovakia; Workers’ Gymnastic Union; Communist Physical Education; Orel; Sokol; Gymnastic Movement